HIV-associated photodermatitis in African populations - Isaacs, Thuraya; Lehloenya, Rannakoe (Frontiers in Allergy, 2023)
Photosensitive dermatoses are seen in 5% of HIV-infected persons. These include drug- and chemical-induced photoallergic and phototoxic reactions, chronic actinic dermatitis of HIV, photo lichenoid drug eruptions, and porphyria. Data on photodermatitis in HIV are limited to case reports and series. The pathogenesis is not completely understood and includes a th2 phenotype in HIV which results in impaired barrier function and resultant allergen sensitisation as well as immune dysregulation. The objective of this manuscript is to review the literature on the clinical phenotype, pathogenesis, role of photo and patch testing, outcomes, and treatment of photodermatitis in HIV in an African population.